Unleashing the Power of Cold Atmospheric Plasma: Inducing Mitochondria Damage‐Mediated Mitotic Catastrophe - Shengjie Peng; Yue Feng; K.N. Yu; Lijun Wu; Guodong Chen; Miaomiao Yang; Lele Zhao; Wei Cao; Qianwen Cui; Lianjun Chen; Quan Li; Yifan Huang; et al. (Advanced Science)
Abstract Despite the promise of cold atmospheric plasma (CAP) for cancer treatment, the challenges associated with the treatment of solid tumors and penetration depth limitations remain, restricting its clinical application. Here, biological evidence is provided that the killing effect of CAP treatment is confined to less than 500 µm subcutaneously and the actual biological dose decreased gradually with depth for the first time, indicating that the limited penetration depth has become an urgent problem that demands immediate solutions. Significantly, it is showed that different from high‐dose treatments, CAP decreased the doses to the low‐dose range but still exhibited anti‐tumor effects via mitotic catastrophe. Unlike radiotherapy or chemotherapy, low‐dose CAP treatment induces mitochondrial structural damage and dysfunction, disrupts energy metabolism and redox balance, and results in mitotic catastrophe. Collectively, these findings suggest that better understanding and taking full advantage of the dose‐response gradient effect of CAP is a potential strategy to prompt its clinical application beyond improving CAP penetration.